Control of Key Distribution Material Requirements (MDU) in Meeting the Demand for New Installations and Power Changes in Utility Companies - Oktavian Syaputra; Nurhadi Siswanto (International Journal Labs, 2025)
Inventory control in utility companies is crucial due to its potential to improve the achievement of sales revenue ratios in serving New Connection (PB) and Power Change (PD) requests. In inventory management, accurate demand planning is essential to minimize both excess and shortage of materials. The inaccuracy in calculating inventory parameters for Distribution Main Materials (MDU), especially for PB and PD, is primarily due to the lack of consideration for demand uncertainty, often resulting in stockouts or overstock. This study aims to optimize inventory management and minimize MDU inventory costs based on the company's inventory policy by classifying MDU according to criticality levels ABA, ABB, and ABC. Short-term forecasting is conducted using exponential smoothing or double exponential smoothing, selecting the method with the smallest forecasting error. Inventory parameters are calculated using the Continuous Review (s,S) and Periodic Review (R,s,S) methods, compared against the company's current condition, and the most optimal policy is selected under stochastic demand conditions. After selecting the best parameters among the three policies, total inventory cost and Service Level per MDU are calculated using Material Requirement Planning (MRP) simulation. By applying inventory policy parameters using the Periodic Review method (R,s,S), the total inventory cost and Service Level for each MDU classification (ABA, ABB, ABC) vary, with an average inventory cost of IDR 76 billion for ABA, IDR 3.6 billion for ABB, and IDR 844 million for ABC, and a Service Level of 98%. This allows the company to achieve inventory cost savings of up to 70% within 36 months compared to the current condition.